2010
DOI: 10.1083/jcb.200906155
|View full text |Cite
|
Sign up to set email alerts
|

Fate-determining mechanisms in epithelial–myofibroblast transition: major inhibitory role for Smad3

Abstract: Smad3 inhibits activation of the smooth muscle actin promoter and functions as a timer for myogenic programming in the epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
164
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(183 citation statements)
references
References 70 publications
12
164
0
Order By: Relevance
“…Hic-5 interacts with SMAD-family members, altering their stability, and could regulate the biphasic differentiation by terminating this early SMADdependent phase and enabling the later MRTF-A-SRF phase (Charbonney et al, 2011;Masszi et al, 2010;Wang et al, 2008Wang et al, , 2005. The reported negative regulation of SMAD7 by Hic-5 might also partially explain the recent finding that Hic-5-knockout mice are resistant to the development of liver fibrosis (Lei et al, 2016).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Hic-5 interacts with SMAD-family members, altering their stability, and could regulate the biphasic differentiation by terminating this early SMADdependent phase and enabling the later MRTF-A-SRF phase (Charbonney et al, 2011;Masszi et al, 2010;Wang et al, 2008Wang et al, , 2005. The reported negative regulation of SMAD7 by Hic-5 might also partially explain the recent finding that Hic-5-knockout mice are resistant to the development of liver fibrosis (Lei et al, 2016).…”
Section: Discussionmentioning
confidence: 59%
“…One way in which SMADs are thought to regulate the induction of contractile genes important for myofibroblast differentiation is by regulating the expression and function of MRTF-A (Charbonney et al, 2011;Masszi et al, 2010;Mihira et al, 2012;Morita et al, 2007;Scharenberg et al, 2014). We observed that MRTF-A levels were significantly lower in SMAD3-depleted NHDFs at 48 h post treatment (Fig.…”
Section: Hic-5 Expression In Myofibroblasts In Vivomentioning
confidence: 50%
See 1 more Smart Citation
“…Smads have been shown to activate SMC differentiation from several different progenitors (22,26,43,44) although Smad3 was recently reported to inhibit MRTF-induced ACTA2 expression in epithelial-myofibroblast transition (45). It appears that only Smad3, but not Smad2, mediates the suppression of Myocd expression.…”
Section: Discussionmentioning
confidence: 99%
“…Ref. 38). Forty-eight hours after transfection, HA-ERK2 was precipitated through the tag from lysates of untreated or TNF-␣-treated cells.…”
Section: Tnf-␣-induced Erk and Rhoa Activation Is Src-dependent-mentioning
confidence: 99%